2014
DOI: 10.1590/0102-311x00009113
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da dieta e fatores associados entre idosos: estudo de base populacional em Campinas, São Paulo, Brasil

Abstract: O objetivo foi avaliar a qualidade da dieta de idosos segundo variáveis sociodemográficas, comportamentos relativos à saúde e morbidades. Trata-se de estudo transversal de base populacional em amostra de 1.509 idosos, obtida por inquérito de saúde conduzido em 2008-2009, em Campinas, São Paulo, Brasil. A qualidade alimentar foi avaliada pelo Índice de Qualidade da Dieta Revisado (IQD-R). Foram estimadas médias do IQD-R segundo as variáveis independentes e desenvolvido modelo de regressão linear múltipla para a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
2
46

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 30 publications
6
32
2
46
Order By: Relevance
“…As there was no study that evaluated dietary intake in Cd patients, we compared our findings to general studies that evaluated dietary intake and diet quality by BHEI-R. Since most patients in this study were older, a population-based study of 1,509 elderly 39 aimed at assessing quality diet of the elderly according to sociodemographic variables, behaviors related to health and morbidities was considered. Assumpção et al 39 showed similar population characteristics that were found in the present study, a higher proportion of women (57%) and elderly (53.8%) and an average of BHEI-R score 62.4.…”
Section: Dietary Adequacy Of Minerals (% Of Ear)mentioning
confidence: 99%
See 1 more Smart Citation
“…As there was no study that evaluated dietary intake in Cd patients, we compared our findings to general studies that evaluated dietary intake and diet quality by BHEI-R. Since most patients in this study were older, a population-based study of 1,509 elderly 39 aimed at assessing quality diet of the elderly according to sociodemographic variables, behaviors related to health and morbidities was considered. Assumpção et al 39 showed similar population characteristics that were found in the present study, a higher proportion of women (57%) and elderly (53.8%) and an average of BHEI-R score 62.4.…”
Section: Dietary Adequacy Of Minerals (% Of Ear)mentioning
confidence: 99%
“…Since most patients in this study were older, a population-based study of 1,509 elderly 39 aimed at assessing quality diet of the elderly according to sociodemographic variables, behaviors related to health and morbidities was considered. Assumpção et al 39 showed similar population characteristics that were found in the present study, a higher proportion of women (57%) and elderly (53.8%) and an average of BHEI-R score 62.4. In the Assumpção's study, a different method of dietary assessment, using a 24-hour recall, was used, while in this study, FFQ was used.…”
Section: Dietary Adequacy Of Minerals (% Of Ear)mentioning
confidence: 99%
“…Confrontados aos idosos que nunca fumaram, os tabagistas apresentaram pior qualidade da dieta (ASSUMPÇÃO, 2014) ! 76!…”
Section: ! 73!unclassified
“…Por outro lado, o aumento de doenças, paralelamente ao avanço da idade, em ambos os sexos, tende a modificar e melhorar a qualidade da alimentação (ASSUMPÇÃO, 2014).…”
Section: ! 73!unclassified
See 1 more Smart Citation